Exploring Students Engagement in Learning Vocabulary through The Use of Total Physical Response (TPR) Method - Pitaloka, Dewi Ayu Dyah; Wigati, Fikri Asih; Suryaman, Maman (Journal of Educational Sciences, 2025)
The study aims to explore student involvement in vocabulary learning through the Total Physical Response (TPR) method. The TPR method combines physical movement with language learning processes, which are believed to improve student memory and understanding. This research uses a qualitative approach to the design of case studies. The study collected data through observations, interviews, and pre- and post-test vocabulary tests. The results showed that students showed positive engagement, both behavioral, emotional, and cognitive. Significant improvements in vocabulary skills also increased, as seen from the average student vocabulary test score after the application of the TPR method, from 38.55 on the pretest to 81.11 on the posttest. Observations and interviews revealed that students were more active and involved in the learning process, showing a higher interest and positive response to TPR methods. In addition, physical movements associated with vocabulary learning help students memorize and understand vocabulary better.